Determining factors affecting the medical interns' choice of specialties among governmental universities in Riyadh - Ahmed Tariq Al Suwaidan; Lama Abdullah Al Luhidan; Khaled Abdullah Al Barrak; Rehab Abdullah Al Mubrick; Hessah Ibrahim Al Suwaidan; Rawan Abdulaziz Al Shammari; Rima MHD Belal Barakeh; Moath Khalid Al-Ghusoon; Bander Munir Al Rwaily; Sulaiman Abdullah Al Shammari (Wolters Kluwer Medknow Publications, 2021)
The nature of experience during the medical study at university may play an essential role in choosing the specialty. Background: The aim of this study is to determine the effect of national universities in general and on medical interns' career choice, taking into consideration the gender difference. Furthermore, to find out when national universities educate their students about the different specialties. Methods: This was a cross-sectional study that included 234 Saudi medical intern students from four different medical colleges in national universities in Riyadh. These were King Saud University, Princess Nourah Bint Abdulrahman University (PNU), Imam Mohamed Bin Saud Islamic University, and King Saud bin Abdulaziz for Health and Science (KSAU-HS) with consideration of gender differences and availability. All participants who are selected randomly completed an online questioner with a unique code. Results: Around two-thirds (66%) of the participants ensured that their national universities had a positive influence in choosing the specialties dividing equally between both genders. According to the participants' perceptions, all the items of the medical education system did not affect in choosing the specialty except three of them that have a positive effect which are elective experience (43.59%), clinical year (40.6%), and the personality of instructor (38.46%). Furthermore, one-third (33%) of the participants emphasized that their universities educated them about the specialties in the 3rd year. The most common decisive factor was an elective experience of 19.36%, whereas the most common negative factors were improper block duration and the personality of the instructor by 14.52%. Conclusion: Most national universities had a positive effect on their students' career choice, and they educated pregraduate students about specialties.